Influence of Cultural Diversity and Identity on Fashion Expression and Communication in Mexico - Mateo, Alejandro (International Journal of Fashion and Design, 2024)
Purpose: The aim of the study was to investigate the influence of cultural diversity and identity on fashion expression and communication in Mexico. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: In Mexico, cultural diversity and identity profoundly influence fashion expression and communication. Traditional garments like the rebozo and huipil blend indigenous, European, and mestizo influences, creating a vibrant and eclectic fashion scene. Fashion serves as a form of cultural expression, preserving heritage and resisting global homogenization. Fashion communication in Mexico emphasizes social status and identity, with events and social media platforms playing crucial roles in showcasing designs and connecting communities. Unique Contribution to Theory, Practice and Policy: Social identity theory, cultural appropriation theory & intersectionality theory may be used to anchor future studies on the influence of cultural diversity and identity on fashion expression and communication in Mexico. Foster collaboration between fashion designers, cultural experts, and communities to create more inclusive and culturally sensitive fashion practices. Advocate for policies and guidelines that promote ethical and culturally sensitive fashion practices.